MODEL KADERISASI PDIP DALAM MENGHADAPI PEMILU LEGISLATIF 2009 - Aryojati Ardipandanto (Jurnal Politica, 2011)
Facing Legislative Election 2009, PDIP practices caderization method that emphasizing the aspect of Party ideology, but as a matter of fact this is not supported by giving substance or matter of caderization that giving attention to increasing quality and capability of each Cader of PDIP itself individually, especially in circumtances of leadership, disipline, militancy, and loyalty. This indicates as well there is still a difference of point of view among the Party Leaders in the matter of substances which are needed to be given in each Party caderization programs.